Determination of effective elastic thickness of the colombian andes using satellite-derived gravity data (2010)
Gravity anomaly values derived from Global Geopotential Models (calculated from the CHAMP and GRACE satellite missions), are compared with free air ground gravity data to find the best representation of surface data. Using these values and topographical heights extracted from digital topography models, we applied the isostatic response function (admittance) to a collection of profiles, to find an average of elastic thickness for the Colombian Andes.